Pengaruh Interval Ekstensif dan Fartlek Terhadap Kapasitas Vo2maks Pemain Futsal MUTU FA Kebumen - Syarif, Ahmad; Erfayliana, Yudesta; Utomo, Andy Widhiya Bayu; Sumantri, Riyan Jaya; Mudayat, Mudayat; Widiyono, Ibnu Prasetyo; Yogi Ferdy Irawan, Yogi Ferdy Irawan; Muhafid, Ervian Arif (Jurnal Kridatama Sains dan Teknologi, 2023)
Based on the author's observations in the field, it shows that the VO2max capacity of the MUTU FA Kebumen futsal players is still low. This is possible due to the lack of precise training methods used by trainers in the training process. This study aims to see the effect of extensive interval training and fartlek training on the VO2max capacity of MUTU FA Kebumen futsal players. This research method is a quasi-experimental method (quasi experimental). The population of this study was 30 people, while the sample was taken by purposive sampling so that a sample of 24 players was obtained. The test used is the bleep test which aims to determine the VO2max capacity of futsal players. The results of the data analysis show that: 1) extensive interval method training has a significant effect on the VO2max capacity of MUTU FA Kebumen futsal players; 2) fartlek training has a significant effect on the VO2max capacity of MUTU FA Kebumen futsal players; 3) extensive interval method training provides a more effective effect than fartlek training on increasing the VO2max capacity of MUTU FA Kebumen futsal players.Keywords: Exercise, VO2max, Futsal